PENGARUH LITERASI AKUNTANSI, PENCATATAN TRANSAKSI HARIAN, DAN PENGGUNAAN E-WALLET TERHADAP KUALITAS PENGELOLAAN KEUANGAN - Novianti, Putri; Auliya Zulfatillah (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2025)
This study was conducted to examine the effect of accounting literacy, daily transaction recording, and e-wallet usage on financial management quality. The respondents were MSMEs engaged in the food and beverage sector in Bandung. Although these MSMEs have utilized digital payment systems, there are still obstacles, particularly in terms of inconsistent transaction recording and suboptimal utilization of financial data from e-wallets. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 72 respondents. Statistical testing uses multiple linear regression. The regression analysis results show that the three independent variables, namely accounting literacy, daily transaction recording, and e-wallet usage, have a significant partial effect on financial management quality. However, the negative regression coefficients for all three variables indicate that improper implementation of these aspects can have a negative impact on SME finances. Therefore, a more consistent and accurate understanding and application are needed to ensure that the use of financial technology and transaction recording can truly enhance the overall quality of SME financial management.